Breast manifestations of systemic diseases - Dilaveri CA; Mac Bride MB; Sandhu NP; Neal L; Ghosh K; Wahner-Roedler DL (Dove Medical Press, 2012)
Christina A Dilaveri, Maire Brid Mac Bride, Nicole P Sandhu, Lonzetta Neal, Karthik Ghosh, Dietlind L Wahner-RoedlerDivision of General Internal Medicine, Mayo Clinic, Rochester, MN, USAAbstract: Although much emphasis has been placed on the primary presentations of breast cancer, little focus has been placed on how systemic illnesses may affect the breast. In this article, we discuss systemic illnesses that can manifest in the breast. We summarize the clinical features, imaging, histopathology, and treatment recommendations for endocrine, vascular, systemic inflammatory, infectious, and hematologic diseases, as well as for the extramammary malignancies that can present in the breast. Despite the rarity of these manifestations of systemic disease, knowledge of these conditions is critical to the appropriate evaluation and treatment of patients presenting with breast symptoms.Keywords: breast, endocrine, hematologic, infectious, vascular